Proposal of an applied methodology to the study of urban-solar simulation as a design tool - Longhini, Victoria (Universidad Nacional del Litoral, 2020)
The present work is a summary of a methodological proposal that allows to deal with scientific-quantitative criteria solutions applied to the current problem, covering the issue of the absence of effective architectural-urban design solutions that take advantage or solve the access of natural light and ensure the habitability in urban enclosures allowing its use to capture solar energy. Through simulation, which was developed as a study methodology, the guidelines regarding habitability, health and accessibility guarantees of solar energy, proposed by the Urban Planning Code and its compliance in the Central Area of ​​San Miguel de Tucumán, were reviewed. A systematized simulation process is proposed to analyze the consequences of densification, a product of the construction industry in progress, applying a methodology to investigate the real effects of the implementation of urban planning standards. This allows the analysis of the potential of clean energy production on surfaces exposed to it, the pre-visualization and study of the habitability of high-rise courtyards and the verification of laws that need to be reviewed in order to give a real solution and effective to design and habitability problems.